Development and Application of CRISPR-Cas Based Tools - Hu, Yanping; Li, Wei (Frontiers in Cell and Developmental Biology, 2022)
Abundant CRISPR-Cas systems in nature provide us with unlimited valuable resources to develop a variety of versatile gene editing tools, which are powerful weapons in biological discovery and disease treatment. Here, we systematically review the development of CRISPR gene editing tools from DNA nuclease to RNA nuclease, from nuclease dependent-tools to nucleic acid recognition dependent-tools. Also, considering the limitations and challenges of current gene editing tools, we discuss the potential directions for development of novel gene editing tools in the future.